Effectiveness of Mindful Parenting Training on Parenting Stress and Emotional Self-Regulation in Mothers of Children with Oppositional Defiant Disorder - Mehri, Zahra; Saedi, Sara; Mohammadi Farahmand, Gholamreza; Sabouri Rad, Soma (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The objective of this study was to examine the effectiveness of mindful parenting training on parenting stress and emotional self-regulation in mothers of children diagnosed with oppositional defiant disorder (ODD). Methods and Materials: This study employed a quasi-experimental design with pre-test–post-test and a control group. The statistical population included all mothers of children diagnosed with oppositional defiant disorder who had referred to counseling centers in Tehran. After initial screening and matching, participants were randomly assigned to either the experimental or control group. Standardized questionnaires on parenting stress and emotional self-regulation were utilized as data collection tools. Findings: The results of covariance analysis and repeated-measures ANOVA indicated that the educational intervention led to a significant reduction in parenting stress, improvement in emotional self-regulation, and an increase in psychological capital in the experimental group compared to the control group. Moreover, the observed changes in the variables were significantly explained by the educational intervention, demonstrating the effectiveness of mindful parenting training on the mental health of mothers of children with behavioral disorders. Conclusion: Mindful parenting is effective in reducing parenting stress and enhancing emotional self-regulation in mothers of children with oppositional defiant disorder.